Metabolic plasticity enables lifestyle transitions of Porphyromonas gingivalis - M. Fata Moradali (Nature Portfolio, 2021)
Abstract Our understanding of how the oral anaerobe Porphyromonas gingivalis can persist below the gum line, induce ecological changes, and promote polymicrobial infections remains limited. P. gingivalis has long been described as a highly proteolytic and asaccharolytic pathogen that utilizes protein substrates as the main source for energy production and proliferation. Here, we report that P. gingivalis displays a metabolic plasticity that enables the exploitation of non-proteinaceous substrates, specifically the monocarboxylates pyruvate and lactate, as well as human serum components, for colonization and biofilm formation. We show that anabolism of carbohydrates from pyruvate is powered by catabolism of amino acids. Concomitantly, the expression of fimbrial adhesion is upregulated, leading to the enhancement of biofilm formation, stimulation of multispecies biofilm development, and increase of colonization and invasion of the primary gingival epithelial cells by P. gingivalis. These studies provide the first glimpse into the metabolic plasticity of P. gingivalis and its adaptation to the nutritional condition of the host niche. Our findings support the model that in response to specific nutritional parameters, P. gingivalis has the potential to promote host colonization and development of a pathogenic community.